Identification and Characterization of Three Spore Wall Proteins of Enterocytozoon Bieneusi - Meng, Xinan; Ye, Haojie; Shang, Ziyu; Sun, Lianjing; Guo, Yaqiong; Li, Na; Xiao, Lihua; Feng, Yaoyu (Frontiers in Cellular and Infection Microbiology, 2022)
Enterocytozoon bieneusi is the most common microsporidian pathogen in farm animals and humans. Although several spore wall proteins (SWPs) of other human-pathogenic microsporidia have been identified, SWPs of E. bieneusi remain poorly characterized. In the present study, we identified the sequences of three E. bieneusi SWPs from whole genome sequence data, expressed them in Escherichia coli, generated a monoclonal antibody (mAb) against one of them (EbSWP1), and used the mAb in direct immunofluorescence detection of E. bieneusi spores in fecal samples. The amino acid sequence of EbSWP1 shares some identity to EbSWP2 with a BAR2 domain, while the sequence of EbSWP3 contains a MICSWaP domain. No cross-reactivity among the EbSWPs was demonstrated using the polyclonal antibodies generated against them. The mAb against EbSWP1 was shown to react with E. bieneusi spores in fecal samples. Using chromotrope 2R staining-based microscopy as the gold standard, the sensitivity and specificity of the direct immunofluorescence for the detection of E. bieneusi were 91.4 and 73.7%. Data generated from the study could be useful in the characterization of E. bieneusi and immunological detection of the pathogen.